2018
DOI: 10.1038/s41598-018-36230-5
|View full text |Cite
|
Sign up to set email alerts
|

Cognitively Demanding Object Negotiation While Walking and Texting

Abstract: Cell phone related pedestrian injuries are increasing, but the underlying causes remain unclear. Here, we studied how cell phone use directly affected obstacle avoidance ability. Thirty healthy adults participated. Cognitive capacity was quantified using standard tests. Participants walked on a treadmill in a virtual reality environment with and without performing a texting-like cell phone task. Participants also navigated either ‘no’, ‘simple’ or ‘complex’ object negotiation tasks that directly manipulated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…A recent narrative review of 20 studies, mostly in young healthy adults, concluded that texting was associated with impaired gait performance [10]. Subsequent studies have also shown consistent findings; however, studies continue to be conducted in young adults [11][12][13], or with small sample sizes of as few as 10 participants [12][13][14][15]. Given the increasing use of smartphones and other devices in older age groups [16], the higher dual-task cost of similar activities in older versus younger adults, and the evidence of increasing "pedestrian distraction by technology" [17], there is a need to investigate the impact of texting on walking across age categories.…”
Section: Introductionmentioning
confidence: 99%
“…A recent narrative review of 20 studies, mostly in young healthy adults, concluded that texting was associated with impaired gait performance [10]. Subsequent studies have also shown consistent findings; however, studies continue to be conducted in young adults [11][12][13], or with small sample sizes of as few as 10 participants [12][13][14][15]. Given the increasing use of smartphones and other devices in older age groups [16], the higher dual-task cost of similar activities in older versus younger adults, and the evidence of increasing "pedestrian distraction by technology" [17], there is a need to investigate the impact of texting on walking across age categories.…”
Section: Introductionmentioning
confidence: 99%
“…In this study we examine gait events influenced by cognitive load. This gives insight into which parts of gait is influenced rather than step time using smartphone [5], or mentoring each participants response while walking on a treadmill [23]. The results are promising, but apart from assessing the particular classification accuracy numbers, the main weakness in the conclusions comes from the limited number of subjects yet included in the currently reported starting phase of this work.…”
Section: Discussionmentioning
confidence: 94%
“…Compared to the same postural-locomotor task without using a mobile phone, texting mainly induced a slowdown and increased instability when walking on the ground [7,[13][14][15]20,21,[24][25][26][27][28][29][30][31], on a treadmill [7,[32][33][34][35], with obstacles [36][37][38][39][40][41][42] and on an inclined plane (only when going downhill) [43].…”
Section: Key Resultsmentioning
confidence: 99%